1980
DOI: 10.1055/s-2007-996262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroxine on the Hepatic Glycogen and Glucose-6-Phosphatase Activity of Developing Rats

Abstract: The influence of exogenous thyroxine was studied on the hepatic glycogen content and glucose-6-phosphatase activity of rats of different age groups. The glycogen content and glucose-6-phosphatase activity were found to be decreased in the livers of 5, 15, 30 and 60-day-old rats after thyroxine treatment. In normal rats of 5, 15, 30 and 60-day-old, a gradual rise in both the hepatic glycogen content and glucose-6-phosphatase activity was noted as the age advanced from immature to adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Previous studies in the dog (40) and rat (42) have shown a decrease in both liver and muscle glycogen stores in response to excess thyroid hormones. In man, however, the evidence is more uncertain.…”
Section: Glucose Homeostasismentioning
confidence: 83%
“…Previous studies in the dog (40) and rat (42) have shown a decrease in both liver and muscle glycogen stores in response to excess thyroid hormones. In man, however, the evidence is more uncertain.…”
Section: Glucose Homeostasismentioning
confidence: 83%
“…Hypophysectomized rats treated for 4 days with 0.1 mg T 4 daily also have been shown to increase the glucose-6-phosphatase activity (Harper and Young 1959). The suppression of enzyme activity was found in rats treated with 0.1 mg T 4 for 5 days (Paul and Dhar 1980) as well as in mice receiving T 3 (0.03; 0.3,3 ugm daily) (Winnick 1970) by the intraperitoneal route for 6 days. Considering the animal species employed, nutritional status of animals, type and duration of treatment we have not been able to find a satisfactory explanation for these contradictory reports.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies have demonstrated that the activities of the translocase and hydrolase components of glucose-6-phosphatase is augmented in fasted (Arion andNordlie 1965;Fisher and Stetten 1966;Nordlie, Arion, Hanson, Gildsdorf and Home 1968) and in diabetic animals (Jakobsson and Dallner 1968) and that glucocorticoids and glucagon increase the enzyme activity both in vivo (Arion and Nordlie 1967) and in vitro (Speth and Schulze 1981). The action of thyroid hormones on glucose-6-phosphatase has been previously studied in rats and mice and stimulatory as well as inhibitory effects have been reported (Murad andFreedland 1967,Paul andDhar 1980;Winnick 1970). In the present study we have investigated the effect of thyroxine (T 4 ) and triiodothyronine (T 3 ) on the activities of the translocase and hydrolase components of hepatic glucose-6-phosphatase in fed and fasted rats.…”
mentioning
confidence: 99%
“…6 Hyperthyroidism may aggravate the basic metabolic disturbance in AIP by further increasing hepatic 5-aminolaevulinate (ALA) synthase activity, as physiological levels of thyroid hormones stimulate allylisopropylacetamide-induced porphyrin biosynthesis in chick embryo liver cell culture. 7 Furthermore, hyperthyroidism is a catabolic disease causing an increase in energy demand and depletion in glycogen stores, 8 and starvation is known to precipitate symptomatic AIP. In our patient, both attacks occurred in the luteal phase of the menstrual cycle and recurrent attacks in the late luteal phase can be a major problem.…”
Section: Discussionmentioning
confidence: 99%